Allorhizocola rhizosphaerae gen. nov., sp. nov., a new member of Micromonosporaceae isolated from rhizosphere soil of the plant Calligonum mongolicum. Issue 1 (16th November 2018) - Sun, Ye; Jiang, Zhu-Ming; Zhao, Li-Li; Su, Jing; Yu, Li-Yan; Tian, Yong-Qiang; Zhang, Yu-Qin
Abstract : The taxonomic position of an actinobacterium, designated CPCC 204380 T, which was isolated from a rhizosphere soil sample of the plant Calligonum mongolicum collected from Xinjiang Province, China, was established using a polyphasic approach. Vegetative hyphae developed well and globose bodies formed from aged hyphae. Spore chains that differentiated from the vegetative hyphae contained non-motile rod-shaped spores. The peptidoglycan contained meso -diaminopimelic acid and 3-hydroxydiaminopimelic acid as the diagnostic amino acids. The acyl type of the peptidoglycan was glycolyl. Glucose, mannose, ribose and xylose were detected in whole-cell hydrolysates. The predominant menaquinone was MK-10(H8 ), followed by MK-10(H6 ) and MK-10(H4 ). The polar lipid profile consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol and phosphatidylinositol mannoside. The major fatty acids were iso-C15 : 0, iso-C16 : 0 and C17 : 1 ω9 c . The genomic G + C content was 64.9 mol%. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain CPCC 204380 T should be placed in the family Micromonosporaceae, in which it formed a distinct lineage next to the genera Rhizocola, Catellatospora, Catelliglobosispora, Hamadaea and Allocatelliglobosispora. It shared the highest 16S rRNA gene sequence similarities with Rhizocola hellebori K12-0602 T (96.1 %), Catellatospora chokoriensis 2-25/1 T (95.9 %), Catelliglobosispora koreensis DSM 44566 T (95.9 %), Hamadaea tsunoensis DSM 44101 T (95.3 %) and Allocatelliglobosispora scoriae Sco-B14 T (94.2 %), and less than 94.0 % sequence similarity with other validly described species. The combination of phylogenetic analysis and phenotypic characteristics supported the proposal of strain CPCC 204380 T as representing a novel species of a new genus in the family Micromonosporaceae, for which the name Allorhizocola rhizosphaerae gen. nov., sp. nov. is proposed. CPCC 204380 T (=DSM 102292 T =KCTC 39746 T ) is the type strain of the type species.